Glycerol derived process contaminants in refined coconut oil induce cholesterol synthesis in HepG2 cells. (May 2019) - Liu, Ruijie; Cheng, Min; Kothapalli, Kumar S.D.; Wang, Zhen; Mendralla, Elizabeth; Park, Hui Gyu; Block, Robert C.; Wang, Xingguo; Brenna, J. Thomas
Abstract: Despite its 50-year history, the conventional diet-heart hypothesis holding that dietary saturated fats raise serum cholesterol, and with it, cardiovascular risk, remains controversial. Harsh chemical and physical treatment generates process contaminants, and refined oils raise serum and tissue cholesterol in vivo independent of saturated fat content. We developed an in vitro bioassay for rapidly assessing the influence of oils on cholesterol metabolism in the human liver HepG2 cell line, and tested it using coconut oil (CO) of various stages of refinement. CO was dissolved with dipalmitoyl phosphatidylcholine (DPPC) surfactant, solvent evaporated, and emulsified into fat-free cell culture media. After 24 h treatment cellular cholesterol and triacylglycerol increased; HMG-CoA Reductase (HMGCR) increased and CYP7A1 (cholesterol 7α-hydroxylase) decreased with sequential processing steps, deacidification, bleaching, deodorization, while fatty acid profiles were not affected. Glycerol-derived process contaminants glycidyl esters and monochloropropandiol (MCPD) increased with processing. Addition of glycidyl or MCPD to virgin CO (VCO) had similar effects to processing, while addition of phenolic antioxidants to fully refined CO reduced HMGCR and increased CYP7A1 . We conclude that harsh processing creates contaminants that raise cholesterol levels in vitro, consistent with a role as a contributing atherosclerotic factor. Graphical abstract: Image 1 Highlights: Eating saturated fats are widely believed to raise circulating cholesterol levels. Gently processed (virgin) coconut oil (VCO) does not raise cholesterol. Refining increases human liver cell cholesterol synthesis and reduces degradation. Glycidyl esters and 3-MCPD added to VCO increases cholesterol. Reduction of process contaminants is likely to improve cardiovascular health.